2021
DOI: 10.1111/petr.14061
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center report of COVID‐19 disease course and management in liver transplanted pediatric patients

Abstract: Background In 2019, SARS‐CoV‐2 causing COVID‐19 emerged. Severe COVID‐19 symptoms may evolve by virtue of hyperactivation of the immune system. Equally, immunocompromised patients may be at increased risk to develop COVID‐19. However, treatment guidelines for children following liver transplantation are elusive. Methods As a liver transplantation center, we diagnosed and followed up 10 children (male/female: 8/2) with a median age of 8.5 years (IQR: 5.2–11.0), with COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…A recent metaanalysis of 15 anakinra trials in COVID-19 patients showed a beneficial effect on lowering mortality [107]. Some pediatric liver transplant recipients successfully received anakinra as a part of multi-drug therapy [108]. A study of KTRs showed no significant effect in terms of intensive care unit admission or respiratory secondary infections between anakinra-and tocilizumab-treated groups [109].…”
Section: Il-1 Receptor Antagonistsmentioning
confidence: 99%
“…A recent metaanalysis of 15 anakinra trials in COVID-19 patients showed a beneficial effect on lowering mortality [107]. Some pediatric liver transplant recipients successfully received anakinra as a part of multi-drug therapy [108]. A study of KTRs showed no significant effect in terms of intensive care unit admission or respiratory secondary infections between anakinra-and tocilizumab-treated groups [109].…”
Section: Il-1 Receptor Antagonistsmentioning
confidence: 99%
“…Sin et al [ 18 ] reported a high rate of acute liver injury during a COVID-19 infection and worse outcomes in patients infected in the early period after liver transplantation. In contrast, Yuksel et al [ 10 ] reported that being immunocompromised did not affect disease severity or survival. Despite immunosuppressive treatment, all patients developed antibodies against COVID-19 in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Literature on the clinical features and outcomes of SARS-CoV-2 infection in children with chronic gastrointestinal and liver diseases has mainly focused on three diseases: CLD, liver transplantation recipients, and inflammatory bowel disease [ 8 9 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, data from our study support the fact that immunosuppression, after the critical post-transplant period of 6 months appears not to be a risk factor for the worsening of COVID-19 in PLTR. If there is a beneficial effect of immunosuppression by modulation of the immune system, thus preventing progression to severe forms of the disease, as suggested by uncontrolled observational clinical studies [ 15 , 35 , 36 , 37 , 38 , 39 , 40 ], this should be confirmed soon with comparative and controlled studies. Some limitations of the present study should be noted.…”
Section: Discussionmentioning
confidence: 99%